2023
DOI: 10.1002/agt2.387
|View full text |Cite
|
Sign up to set email alerts
|

A sandwiched luminescent heterostructure based on lanthanide‐doped Gd2O2S@NaYF4 core/shell nanocrystals

Dengfeng Yang,
Wei Zheng,
Ping Huang
et al.

Abstract: Lanthanide (Ln3+) oxysulfide nanocrystals (NCs) have great prospect in many advanced technologies; however, they suffer from a low photoluminescence efficiency due to the volatility of sulfur and deleterious surface quenching effect. Herein, we report a novel sandwiched luminescent heterostructure based on Ln3+‐doped Gd2O2S@NaYF4 core/shell NCs with tunable sulfur content in the sandwich layer. By means of Eu3+ as the sensitive structural probes, we unravel the ligand‐mediated structure control of the NCs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In principle, the upconversion mechanisms involving lanthanides can be mainly categorized into five classes: excited-state absorption, energy transfer upconversion, cooperative upconversion and photon avalanche. 19,[64][65][66][67][68] Here, we focus on the mechanisms of energy transfer upconversion. Fluorescence upconversion of lanthanides (e.g., Er 3+ , Tm 3+ , and Ho 3+ ) is usually realized via ETU, 19,20 where long-lived intermediate states exist to store energy (Fig.…”
Section: Energy Transfer Mechanismmentioning
confidence: 99%
“…In principle, the upconversion mechanisms involving lanthanides can be mainly categorized into five classes: excited-state absorption, energy transfer upconversion, cooperative upconversion and photon avalanche. 19,[64][65][66][67][68] Here, we focus on the mechanisms of energy transfer upconversion. Fluorescence upconversion of lanthanides (e.g., Er 3+ , Tm 3+ , and Ho 3+ ) is usually realized via ETU, 19,20 where long-lived intermediate states exist to store energy (Fig.…”
Section: Energy Transfer Mechanismmentioning
confidence: 99%
“…However, at the nanoscale, their application is greatly limited due to the volatility of sulfur and harmful surface quenching. Qilin Zou et al 64 and Dengfeng Yang et al 65 epitaxially grew a layer of inert NaYF 4 shell on the surface of Gd 2 O 2 S NPs (Fig. 4b).…”
Section: Classification By Matrixmentioning
confidence: 99%
“…Zhang et al reported a multilayered core-shell nanostructure, NaGdF 4 : Yb/Tm/Er@NaGdF 4 : Eu@NaYF 4 , which emits emission covering the entire visible range and can be combined to produce white light by optimizing the photon leap paths of specific lanthanide ions [92]. Yang and his research team proposed an innovative rare-earth sulfide/fluoride heterostructure design, which achieves efficient multicolor upconversion and downshift luminescence of rare-earth ions at a single excitation wavelength by skillfully doping different kinds of rare-earth ions [93].…”
Section: Homogeneous Core-shell Structurementioning
confidence: 99%